2018
DOI: 10.1590/0104-1428.09917
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of amylose plasticized with Brazilian Cerrado oils: part I

Abstract: ObstractBiodegradable polymers have become part of the realm of polymer science with specially when associated to renewable sources. Unraveling the plasticizer effect of natural occurring fatty acids in the Brazilian Cerrado on amylose oligomers was aimed in this work in an aqueous environment. Since the interactions within a material are of extreme importance to its molecular behavior, the main focus was directed to the molecular interactions whether intra or intermolecular type. Molecular Mechanics and Dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…16 Further investigation of starch at the molecular scale has provided a detailed description of the structure and organization of the main amylose (e.g., molecular weight distribution, single and double helical structure) and amylopectin (e.g., unit chain distribution and organization into clusters) components. 20 In support of accompanying experimental data, molecular simulations can provide further insight in the molecular scale structure and physical properties of a material. 21,22 So far, computational studies have focused mainly on simulations of low molecular weight amylose chains in solution.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…16 Further investigation of starch at the molecular scale has provided a detailed description of the structure and organization of the main amylose (e.g., molecular weight distribution, single and double helical structure) and amylopectin (e.g., unit chain distribution and organization into clusters) components. 20 In support of accompanying experimental data, molecular simulations can provide further insight in the molecular scale structure and physical properties of a material. 21,22 So far, computational studies have focused mainly on simulations of low molecular weight amylose chains in solution.…”
Section: Introductionmentioning
confidence: 84%
“…Various experimental studies have focused on understanding the microstructure and the underlying nanostructure of starch from the granules (on the scale of several micrometers) down to growth rings (with length of around 0.1 μm), blocklets, and crystalline and amorphous lamellae (of characteristic size 8–11 nm). The majority of these studies have also revealed key links of the structure to its functional properties such as the gelatinization mechanism ,,, or sensory attributes . Further investigation of starch at the molecular scale has provided a detailed description of the structure and organization of the main amylose (e.g., molecular weight distribution, single and double helical structure) and amylopectin (e.g., unit chain distribution and organization into clusters) components . In support of accompanying experimental data, molecular simulations can provide further insight in the molecular scale structure and physical properties of a material. , So far, computational studies have focused mainly on simulations of low molecular weight amylose chains in solution. These include mostly studies of conformation, flexibility and dynamics of disaccharides in water and in the presence of lipids or oligomer chain conformational properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the chemical constituents of a material are known, morphological and physical properties have been successfully predicted using simulation for a wide range of materials (Steinhauser and Hiermaier 2009) . Molecular simulations of single amylose molecules have revealed key physical aspects of lipid binding, while more rigorous studies focusing on disaccharide dynamics have investigated the reliability of modern force fields in simulating conformational dynamics (López, de Vries, and Marrink 2012;Perić-Hassler et al 2010;Galvelis, Re, and Sugita 2017;Kuttel and Naidoo 2005;Y.-C. Wang et al 2014;Turupcu and Oostenbrink 2017;Momany, Willett, and Schnupf 2009;Silva et al 2018;Mishra et al 2014;Kilburn et al 2005;Cheetham, Dasgupta, and Ball 2003;Naidoo and Kuttel, n.d.) . While these studies have greatly enhanced our understanding of starch nanostructure at the single molecule level in solution, they do not address morphological or thermophysical properties of amorphous starch.…”
Section: Introductionmentioning
confidence: 99%
“…If the chemical constituents of a material are known, morphological and physical properties have been successfully predicted using simulation for a wide range of materials (Steinhauser and Hiermaier 2009) . Molecular simulations of single amylose molecules have revealed key physical aspects of lipid binding, while more rigorous studies focusing on disaccharide dynamics have investigated the reliability of modern force fields in simulating conformational dynamics (López, de Vries, and Marrink 2012;Perić-Hassler et al 2010;Galvelis, Re, and Sugita 2017;Kuttel and Naidoo 2005; Y.-C. Wang et al 2014;Turupcu and Oostenbrink 2017;Momany, Willett, and Schnupf 2009;Silva et al 2018;Mishra et al 2014;Kilburn et al 2005;Cheetham, Dasgupta, and Ball 2003;Naidoo and Kuttel, n.d.) . While these studies have greatly enhanced our understanding of starch nanostructure at the single molecule level in solution, they do not address morphological or thermophysical properties of amorphous starch.…”
Section: Introductionmentioning
confidence: 99%